Targeting Hepatic Stellate Cells for the Treatment of Liver Fibrosis by Natural Products: Is It the Dawning of a New Era? - Chan, Yau-Tuen; Wang, Ning; Tan, Hor Yue; Li, Sha; Feng, Yibin (Frontiers in Pharmacology, 2020)
Liver fibrosis is a progressive liver damage condition that worth widely studied. It is important to target and alleviate the disease at early stage, before turning into later cirrhosis or liver cancer. There are currently no direct medicines targeting the attenuation or reversal of liver fibrosis, and so there is an urgent need to look into this area. Traditional Chinese Medicine has a long history in using herbal medicines to treat liver diseases including fibrosis. It is time to integrate the ancient wisdom with modern science and technology, to look for the best solution to the disease. In this review, the principal concept of the pathology of liver fibrosis will be described, and then some of the single compounds isolated from herbal medicines, including salvianolic acids, oxymatrine, curcumin, tetrandrine, etc. will be discussed from their effects to the molecular mechanism behind. Molecular targets of the compounds are analyzed by network pharmacology approach and TGFβ/SMAD was identified as the most common pathway. This review serves to summarize the current findings of herbal medicines combining with modern medicines in the area of fibrosis. It is hopefully to provide insights in further pharmaceutical research directions.